2019
DOI: 10.3961/jpmph.18.170
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding Tuberculosis in Timor-Leste: Results From the Demographic and Health Survey 2016

Abstract: Objectives The aim of this study was to assess knowledge, attitudes, and practices regarding tuberculosis (TB) in the general population in Timor-Leste. Methods In the nationally representative cross-sectional 2016 Timor-Leste Demographic and Health Survey, 4622 men (aged 15-59 years) and 12 607 women (aged 15-49 years) were randomly selected using stratified multistage sampling and interviewed. Results Overall, 66.9% of men and 62.8% of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
6
11
3
Order By: Relevance
“…In agreement with previous studies [26][30] [35], this study found that respondents who had exposed to television, radio and newspaper, being in professional/technical/managerial, having knowledge that TB can be cured and being urban dwellers were associated with correct knowledge about TB transmission. It is reported that, the media form a crucial role in patients' knowledge about TB and, therefore, underscores the requisite for TB health education programmes among disadvantaged households [25] [54].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies [26][30] [35], this study found that respondents who had exposed to television, radio and newspaper, being in professional/technical/managerial, having knowledge that TB can be cured and being urban dwellers were associated with correct knowledge about TB transmission. It is reported that, the media form a crucial role in patients' knowledge about TB and, therefore, underscores the requisite for TB health education programmes among disadvantaged households [25] [54].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with prior literature [46] Eventually, improved levels of education in the community can improve cognitive level and increase the general knowledge about infection control including TB and the general health of the people [51]. Furthermore, as with previous literature [26] [35], the current study found that respondents from the richest households had high chances of having correct knowledge about TB transmission. Generally, the an explanation to this nding might be that, people from households with better income, usually tend to have higher probability of acquiring improved health knowledge and better health seeking behavior [52] [53].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nearly half of migrants and seasonal farm workers had a favorable attitude. This finding is lower than a study conducted in Timor Leste (83.3% in men and 88.6% in women) (31). This could be due to the difference in defining the outcome variable.…”
Section: Discussioncontrasting
confidence: 76%
“…Nearly half of migrants and seasonal farmworkers had a favorable attitude. This nding is lower than a study conducted in Timor Leste (83.3% in men and 88.6% in women) (32). This could be due to the difference in de ning the outcome variable.…”
Section: Discussioncontrasting
confidence: 75%